2015
DOI: 10.14309/crj.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Colitis Mimicking Rectal Carcinoma in a Young Immunocompetent Patient

Abstract: Cytomegalovirus (CMV) infection is often seen in immunocompromised patients. Rarely, immunocompetent patients may present with CMV as a self-limiting, flu-like illness, though a few cases of significant organ-specific complications have been reported in these patients. We report a case in which a previously healthy man presented with hematochezia and an obstructing rectal mass thought to be rectal adenocarcinoma. Biopsy was positive for CMV, which was treated with full resolution of rectal mass confirmed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The differential diagnosis of rectal masses in patients with HIV is broad and includes infectious causes, such as lymphogranuloma venereum, syphilis, CMV, and HHV-8 [1,2,3]. Non-infectious pathologies, such as lymphoma or squamous cell carcinoma, are also important entities to consider in this population [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of rectal masses in patients with HIV is broad and includes infectious causes, such as lymphogranuloma venereum, syphilis, CMV, and HHV-8 [1,2,3]. Non-infectious pathologies, such as lymphoma or squamous cell carcinoma, are also important entities to consider in this population [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Historically it was reported that patients with CMV proctitis can present with rectal ulcers [9] . Upon literature review several case reports make mention of CMV colitis mimicking colorectal malignancy [10] , [11] , [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal ulcers are more common distally and usually have discrete borders, but they can be confluent and span up to 10 cm [52]. CMV rarely elicits an exuberant inflammatory reaction that simulates malignancy [53]. CMV infection is associated with variable inflammatory changes depending on the immune status of the patient.…”
Section: Hiv and Aidsmentioning
confidence: 99%